The role of individual ambidexterity for organizational performance: examining effects of ambidextrous knowledge seeking and offering - Benedikt Schnellbächer; Sven Heidenreich (The Journal of Technology Transfer, 2020)
Empirical research has confirmed positive effects of organizational ambidexterity for companies' long-term performance. More recent research has shifted the focus from organizational level exploration and exploitation to the individual in order to understand psychological micro-foundations of individual ambidexterity. However, our current knowledge on how knowledge flows within individual ambidexterity are initiated and affect performance outcomes is limited. This study thus strives to shed light on the topic by introducing two mechanisms, namely ambidextrous knowledge seeking and ambidextrous knowledge offering, that capture how knowledge flows within individual ambidexterity are initiated. Based on survey-data from 415 employees, findings from structural equation modeling provide first empirical evidence that the focal constructs significantly affect knowledge accumulation on the department level as well as its performance. Finally, results from additional moderation analysis indicate, that ambidextrous knowledge offering leads to higher performance effects in environments characterized by the pursuit of radical innovations, while ambidextrous knowledge seeking is rather suited for environments with a focus on innovating incrementally.
Keywords: O32; D80; D83; 600; Exploration; Exploitation; Radical innovation